VISUAL JOURNALING: BLENDING ILLUSTRATION AND REFLECTION IN ENGLISH CLASSES - Abduvalieva Jasmina Jahongir qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Visual journaling is an engaging and impactful pedagogical approach that combines the power of illustration with the reflective practice of journaling. This article explores the integration of visual journaling into English language arts classrooms, highlighting its ability to enhance student learning, self-expression, and critical thinking. Through the incorporation of drawing, sketching, and other visual elements, students are encouraged to explore course content, process their experiences, and deepen their understanding of literary works and themes. The article discusses the theoretical foundations of visual journaling, provides practical strategies for implementation, and shares insights from educator experiences. By bridging the realms of visual art and written reflection, visual journaling offers a multifaceted approach to nurturing students' creativity, communication skills, and overall engagement with the English curriculum.